Mars Thermospheric Variability Revealed by MAVEN EUVM Solar Occultations: Structure at Aphelion and Perihelion and Response to EUV Forcing. Issue 9 (3rd September 2018) - Thiemann, E. M. B.; Eparvier, F. G.; Bougher, S. W.; Dominique, M.; Andersson, L.; Girazian, Z.; Pilinski, M. D.; Templeman, B.; Jakosky, B. M.
Abstract: The Mars thermosphere holds clues to the evolution of the Martian climate and has practical implications for spacecraft visiting Mars, which often use it for aerobraking upon arrival, or for landers, which must pass through it. Nevertheless, it has been sparsely characterized, even when past accelerometer measurements and remote observations are taken into account. The Mars Atmosphere and Volatile EvolutioN (MAVEN) orbiter, which includes a number of instruments designed to characterize the thermosphere, has greatly expanded the available thermospheric observations. This paper presents new and unanticipated measurements of density and temperature profiles (120–200 km) derived from solar occultations using the MAVEN Extreme Ultraviolet (EUV) Monitor (EUVM). These new measurements complement and expand MAVEN's intended thermospheric measurement capacity. In particular, because the local time is inherently fixed to the terminator, solar occultations are ideally suited for characterizing long‐term and latitudinal variability. Occultation measurements are made during approximately half of all orbits, resulting in thousands of new thermospheric profiles. The density retrieval method is presented in detail, including an uncertainty analysis. Altitude‐latitude maps of thermospheric density and temperature at perihelion and aphelion are presented, revealing structures that have not been previously observed. Tracers of atmospheric dynamics are also observed, including (1) a high altitude polar warming feature at intermediate latitudes, (2) cooler temperatures coinciding with increased gravity wave activity, and (3) an apparent thermostatic response to solar EUV heating during a solar rotation, which shows heating at high altitudes that is accompanied by cooling at lower altitudes. Plain Language Summary: Solar extreme ultraviolet (EUV) radiation is the primary energy source for the thermosphere, the uppermost region of the Mars atmosphere. The Mars Atmosphere and Volatile EvolutioN (MAVEN) orbiter is equipped with the EUV Monitor (EUVM) to track how this region of the spectrum varies. Because EUV radiation is entirely absorbed in the thermosphere, it can be used to probe this region of the atmosphere when the Sun sets or rises over the horizon as viewed from MAVEN using the solar occultation technique. This study presents new temperature and density measurements of the Mars thermosphere made by EUVM solar occultations, which include the first observations of both expected and unexpected phenomena. This includes a warming trend at intermediate altitudes in the winter hemisphere and a cooling trend in the lower thermosphere in response to a relatively rapid increase in solar EUV radiation. These results will aid our understanding of how the Mars upper atmosphere has evolved over time and, in particular, how significant fractions of the atmosphere have been lost to space. Further, these results provide valuable data for mission planners to aid in orbit determination and entry into the atmosphere by landers, both manned or unmanned. Key Points: A high altitude polar warming feature is observed at intermediate northern latitudes near perihelion Heating and cooling above and below 150 km, respectively, is observed that coincides with 27‐day solar EUV variability The mean temperature sensitivity to EUV forcing is found to be 45 ± 12 K·m 2 ·mW −1 at the terminator, independent of dawn or dusk location